Invasive Surgical Techniques in the Mediastinal Staging in Non-Small Cell Lung Cancer - Ozyurtkan, Mehmet Oguzhan (Bentham Science Publ, 2013)
Non-small cell lung cancer is the most common malignancy in the world and accounts for an estimated 1 million deaths each year. Metastasis to the mediastinal lymph nodes is one of the most important factors in determining resectability and prognosis. It also influences staging algorithms. Non-invasive radiographic imaging investigations have their limitations, so tissue sampling is needed. Sampling can be achieved both by invasive surgical or non-surgical techniques. According to the ESTS guidelines, among invasive surgical techniques, mediastinoscopy is still considered to be the gold standard in the mediastinal staging in non-small cell lung cancer. This chapter deals with invasive surgical techniques.
Keywords: Invasive staging; lung cancer; mediastinoscopy